Managing and using information systems : a strategic approach - Pearlson, Keri E.; Saunders, Carol S.; Galletta, Dennis F. (Hoboken, NJ, Amherst, MA : Wiley ; University of Massachusetts Amherst, 2016)
Managers do not have the luxury od abdicating participation in decisions regarding information systems (IS). Managers who choose to do risk limiting their future business options.
Chapter 1. the information systems strategy triangle -- Chapter 2. strategic use of information resources -- Chapter 3. Organizational strategy and information systems -- Chapter 4. digital systems and the design of work -- Chapter 5. information systems and business transformation -- Chapter 6. architecture and infrastructure -- Chapter 7. security -- Chapter 8. the business of information technology -- Chapter 9. governance of the information systems organization -- Chapter 10. information system sourcing -- Chapter 11. managing IT projects -- Chapter 12. business intelligence, knowledge management, and analytics -- Chapter 13. privacy and ethical considerations in information.
Includes index.
Keywords: INFORMATION TECHNOLOGY